2012
DOI: 10.1111/j.1447-0594.2011.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for a 6‐year decline in physical disability and functional limitations among elderly people with type 2 diabetes in the Japanese elderly diabetes intervention trial

Abstract: Aim: Type 2 diabetes increases the risk of disability. The purpose of this study was to clarify the explanatory factors for disability in Japanese diabetic elderly. Methods:The 6-year decline in physical disability and functional limitations was investigated among 317 elderly people with type 2 diabetes recruited in a large-scale prospective study of the Japanese Elderly Diabetes Intervention Trial. Information about diabetes, blood examinations and complications was obtained, and basic activities of daily liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
(114 reference statements)
6
25
0
Order By: Relevance
“…Microvascular injury induced by hyperglycemic damage could progress to the peripheral nerves before patients become aware of any symptoms. Furthermore, latent DPN is known to accrue before symptom manifestation, up to 50% of DPN might be asymptomatic, and DPN has been identified as a risk factor for lower extremity physical disability and functional limitation . The results of the current study are consistent with these findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Microvascular injury induced by hyperglycemic damage could progress to the peripheral nerves before patients become aware of any symptoms. Furthermore, latent DPN is known to accrue before symptom manifestation, up to 50% of DPN might be asymptomatic, and DPN has been identified as a risk factor for lower extremity physical disability and functional limitation . The results of the current study are consistent with these findings.…”
Section: Discussionsupporting
confidence: 87%
“…6 In contrast, diabetes involving episodes of hypoglycemia was also a risk factor for reduced cognitive function and the incidence of dementia. [7][8][9] Previous Japanese research has examined diabetic neuropathy resulting from a decline in physical function in diabetes patients; [10][11][12][13] however, few studies have considered the relationship between diabetes and lower extremity function or compared community-dwelling older adults with and without diabetes. In addition, functional decline in Japanese community-dwelling older adults with diabetes and prediabetes has not been examined sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that physical activity could help prevent functional limitations in older diabetic individuals with an average HbA1c of 8.5%. 31 Although the average HbA1c among our diabetes patients was much lower, 6.8%, physical activity could effectively maintain physical function.…”
Section: Discussionmentioning
confidence: 72%
“…This result agrees with previous findings, which showed that older adults with diabetes had a higher risk of developing physical disability. 30 , 31 Lower PCS can be interpreted as subjective difficulty with activities in everyday life (eg, walking, climbing, bathing), limitations in carrying out work or daily activities, or pain that interferes with work or daily activities. One pathway to low PCS would be the presence of cardiovascular disease and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor : Older people with diabetes mellitus frequently have functional impariment, but there are few reports of the protective effects of longitudinal interventions on functional decline in older people newly diagnosed according to an oral glucose tolerance test (OGTT) . The association between glucose intolerance and decline in instrumental activities of daily living (IADL) was examined to verify the hypothesis that annual education on lifestyle modification can help prevent IADL decline in people with glucose intolerance in a 5‐year longitudinal study.…”
mentioning
confidence: 99%